Analisis Kapasitas Fiskal dan Pengeluaran Pemerintah terhadap Pertumbuhan Ekonomi di Provinsi Nusa Tenggara Barat Tahun 2019-2023 - Kurniati Kurniati; Subhan Purwadinata (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the effect of fiscal capacity and government expenditure on economic growth in West Nusa Tenggara Province from 2019 to 2023, both partially and simultaneously. Economic growth in West Nusa Tenggara (NTB) has not been evenly distributed across the region, and fiscal capacity along with government expenditure are important factors in driving economic growth. This research employs a quantitative associative approach. Panel data, which combines time series and cross-sectional data, was used with the assistance of Eviews 10 software. The results indicate that fiscal capacity has a negative and insignificant effect on economic growth, while government expenditure has a significant positive effect. Simultaneously, fiscal capacity and government expenditure significantly influence economic growth in West Nusa Tenggara during the 2019–2023 period. These findings emphasize the importance of optimizing fiscal capacity and enhancing the effectiveness of government expenditure in regional development. Therefore, local governments are expected to improve the efficiency of fiscal capacity management and government spending to promote sustainable economic growth in NTB.